(untitled) (Research, Society and Development, 2020)
The tegus are generalists lizards that use large amounts of prey in its diet, providing environmental services as a biological controller and seed disperser, which reveals how important diet studies are to understand ecological relationships related to a particular species. So the objective of this study was to analyze diet and food ontogeny of T. matipu, investigating changes in the pattern and composition of food items in different age classes and how the species shares its intraspecific niche. The captured specimens had the contents of their digestive tracts were analysed qualitatively and quantitatively. Our results indicate that T. matipu is a generalist lizard, consuming many food items, which fruits are the most important item in its diet. However, the species uses food resources in different importance proportions, according to its age class. Fruit consumption tends to increase and arthropods consumption decline as the age class increase. Thus, T. matipu performs an intraspecific sharing of feeding niche between the age classes and constitutes potential seed dispersers in its populations distributed along the Upper Course of the Paraguai River.